Studying Indonesian-Speaking Politeness for Class XI Students at SMK Negeri Tapango, Polman Regency - Randi Pratama; Munirah; Andi Sukri Syamsuri (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
The main problem in this study is how to use the principle of politeness in student interactions and the types of speech acts contained in the interaction of class XI students at SMK Negeri Tapango. This study aims to describe the use of politeness principles and describe the types of speech acts contained in the interaction of class XI students at SMK Negeri Tapango. This research is a qualitative descriptive study with the subject of verbal interaction of class XI students at SMK Negeri Tapango, Polewali Mandar Regency. Data collection techniques used are observation techniques, note-taking techniques and recording techniques. Data analysis techniques by transcribing data from observations, identifying and clarifying data, copying into data cards, analyzing data cards and concluding. The results of this study indicate the number of utterances collected is 35 utterances. The politeness principles include: (1) maxim of wisdom as many as 6 utterances (2) maxim of generosity as much as 8 (3) maxim of appreciation as many as 3 utterances (4) maxim of simplicity as many as 2 utterances (5) maxim of consensus as many as 11 utterances and (6) maxim of sympathy as much as 5 utterances. The maxim that is widely used is the maxim of consensus. The maxim that is widely used is the maxim of consensus. This shows that the speaker and the interlocutor in the interaction maximize the compatibility of goals or opinions in interacting. While the maxim that is least used in the speech of the students of SMK Negeri Tapango is the maxim of simplicity.